Experimental Study of Basic Mechanical Properties of Short Basalt Fiber Bundle Reinforced Concrete. Issue 1 (1st January 2022) - Shao, JG; Wang, S; Liu, Y; Zhang, P; Tang, GB; Jin, YG; Li, CC
Abstract: In this paper, the mechanical properties of basalt short fiber bundle reinforced concrete (sbfbrc) are designed, and the effects of basalt fiber bundle content and diameter on its compression, splitting and bending properties are studied. The results show that basalt fiber bundle has good dispersion in concrete. The splitting tensile strength and flexural strength of high-strength concrete are significantly improved, but the compressive strength is not significantly improved. The compressive strength of concrete increases first and then decreases. When the fiber bundle content is 0.2%, the compressive strength increases by 6.11%. The splitting tensile strength and bending strength increase with the increase of fiber bundle content. When the fiber bundle content was 0.6%, they increased by 19.54% and 20.32% respectively compared with the reference group. Compared with basalt fiber bundle with diameter of 0.5mm and 0.8mm respectively, basalt fiber bundle with diameter of 0.2mm has better effect on improving the compressive, splitting, tensile and flexural properties of concrete